Implementation of biopsychosocial supported self‐management for chronic primary oro‐facial pain including temporomandibular disorders: A theory, person and evidence‐based approach. (27th July 2021) - Aggarwal, Vishal R.; Wu, Jianhua; Fox, Frank; Howdon, Daniel; Guthrie, Elspeth; Mighell, Alan
Abstract: Background: Aims of the study were to: Implement supported self‐management for chronic primary oro‐facial pain in a clinical setting. Evaluate its impact on consultation rates, pain severity, interference with life and patient experience. Methods: Sixty‐six patients with chronic primary oro‐facial pain received the intervention at a facial pain clinic at Leeds Dental Institute, UK. Brief Pain Inventory (BPI) scores measured pain severity and interference with life before and after the intervention. Process mining outlined patient care pathways. Monthly consultation rates measured 12 months before and after the intervention were used to evaluate burden on healthcare services and economic impact. Patient feedback was assessed via Patient and Public involvement discussion groups. Results: Mean BPI scores significantly improved after intervention—from 5.70 (SD 1.89) to 3.78 (SD 2.34) ( p  < .001); mean pain interference score reduced from 19.95 (SD 9.41) to 12.05 (SD 9.64) ( p  < .001). Average monthly consultations significantly ( p  = .001) reduced from 0.42/month before the intervention to 0.16/month after the intervention. Economic assessment showed cost savings of £293 per patient per year. Process mining showed high rates of service usage with 31 patients also attending 51 other specialist services between them. Patient and Public Involvement discussion groups with 5 patients identified that the intervention was a 'constant companion' and should be implemented at the outset in the care pathway. Conclusion: Supported self‐management for chronic primary oro‐facial pain has a positive impact on health outcomes (physical functioning, pain intensity and patient experience), as well as service usage and healthcare costs when implemented in a secondary care clinical setting. Reconfiguring current care pathways to upscale early implementation of such interventions should be a priority for future testing. Abstract : Supported self‐management for chronic primary orofacial pain, using a biopsychosocial approach, has a positive impact on patient quality of life, service usage and healthcare costs. Reconfiguring current care pathways to upscale early implementation of such interventions should be a priority. This approach will avoid invasive and irreversible management which is often harmful to patients.